MicroRNA-140-5p regulates osteosarcoma chemoresistance by targeting HMGN5 and autophagy - Yichen Meng (Nature Portfolio, 2017)
Abstract Chemotherapy is an important treatment modality for osteosarcoma. However, it often fails because of chemoresistance, especially multidrug resistance. Previously, we found several genes were involved in chemoresistance development. In this report, we used high-throughput microRNA (miRNA) expression analysis to reveal that expression of miR-140-5p was associated with chemosensitivity in osteosarcoma. The exact roles of miR-140-5p in the chemoresistance of osteosarcoma were then investigated, we found that knockdown of miR-140-5p enhanced osteosarcoma cells resistance to multiple chemotherapeutics while overexpression of miR-140-5p sensitized tumors to chemotherapy in vitro. Moreover, in vivo, knockdown of miR-140-5p also increased the osteosarcoma cells resistance to chemotherapy. Luciferase assay and Western blot analysis showed that HMGN5 was the direct target of miR-140-5p which could positively regulated autophagy. Silencing these target genes by siRNA or inhibition of autophagy sensitized osteosarcoma cells to chemotherapy. These findings suggest that a miR-140-5p/HMGN5/autophagy regulatory loop plays a critical role in chemoresistance in osteosarcoma. In conclusion, our data elucidated that miR-140-5p promoted autophagy mediated by HMGN5 and sensitized osteosarcoma cells to chemotherapy. These results suggest a potential application of miR-140-5p in overall survival, chemoresistance prognosis and treatment.